A contemporary case series of Pseudomonas aeruginosa infective endocarditis. Issue 13 (31st March 2023) - Walczak, Andrew; McCarthy, Kate; Paterson, David L.
Abstract : Pseudomonas aeruginosa infective endocarditis (IE) is a rare disease associated with high mortality and complications. Here, we describe a contemporary set of patients aiming to improve the understanding of risk factors, clinical features, treatments, and outcomes. This retrospective case series reviewed cases from 3 tertiary metropolitan hospitals between January 1999 and January 2019. prespecified data were collected for each case, with a review of risk factors, valve involvement, acquisition, treatment, and complications. Fifteen patients were identified over a 20 years period. All patients presented with fever, 5/15 had preexisting prosthetic valve with valvular heart disease in 7/15 patients making it the most common risk factor. Intravenous drug use (IVDU) was the source in only 6/15 cases with healthcare associated infection and left-sided valvular involvement being more common than previous reports both occurring in 9/15 cases. Complications occurred in 11/15 patients with a 30 days mortality of 13%. Surgery was performed in 7/15 patients and 9/15 patients received antibiotic combination therapy. One year mortality was higher in those with increasing age, comorbidities, left-sided valve involvement, presence of predefined complications, and antibiotic monotherapy. Development of resistance occurred in 2 cases that received monotherapy. P aeruginosa IE remains a rare disease with high mortality and secondary complications.